Photoacoustic energy sensor for nanosecond optical pulse measurement - Sang, Pil Gyu; Heo, Junseok; Park, Hui Joon; Baac, Hyoung Won (Sensors (Switzerland), 2018)
We demonstrate a photoacoustic sensor capable of measuring high-energy nanosecond optical pulses in terms of temporal width and energy fluence per pulse. This was achieved by using a hybrid combination of a carbon nanotube-polydimethylsiloxane (CNT-PDMS)-based photoacoustic transmitter (i.e., light-to-sound converter) and a piezoelectric receiver (i.e., sound detector). In this photoacoustic energy sensor (PES), input pulsed optical energy is heavily absorbed by the CNT-PDMS composite film and then efficiently converted into an ultrasonic output. The output ultrasonic pulse is then measured and analyzed to retrieve the input optical characteristics. We quantitatively compared the PES performance with that of a commercial thermal energy meter. Due to the efficient energy transduction and sensing mechanism of the hybrid structure, the minimum-measurable pulsed optical energy was significantly lowered, ~157 nJ/cm2, corresponding to 1/760 of the reference pyroelectric detector. Moreover, despite the limited acoustic frequency bandwidth of the piezoelectric receiver, laser pulse widths over a range of 6–130 ns could be measured with a linear relationship to the ultrasound pulse width of 22–153 ns. As CNT has a wide electromagnetic absorption spectrum, the proposed pulsed sensor system can be extensively applied to high-energy pulse measurement over visible through terahertz spectral ranges.
Keywords: Optical characteristics; Optical energy; Optical pulse measurement; Photoacoustic sensors; Piezoelectric receivers; Pyro-electric detectors; Terahertz spectral range; Ultrasound sensors; CNT-PDMS; Nanosecond optical pulse; Optical energy meter; Photoacoustic sensor; Ultrasound sensor